Comparison of the antibacterial efficiency of propolis samples from different botanical and geographic origins with and without standardization - Letullier, C.; Manduchet, A.; Dlalah, N.; Hugou, M.; Georgé, S.; Sforcin, J. M. [UNESP]; Cardinault, N. (Taylor & Francis, 2020)
Propolis is a resinous product made by bees and has attracted the attention of researchers for decades due to its numerous biological properties (antimicrobial, antioxidant, anti-inflammatory, immunomodulatory, etc.). Studies have demonstrated that polyphenols may be involved in such effects, although each propolis sample has its own phenolic profile which is related to its botanical origin. Several studies have investigated the biological efficiency of different kinds of propolis extracts obtained from distinct botanic sources, using different extraction ratios and types of solvent, that complicates or even makes it impossible to objectively compare the results and to remove irrelevant information from it, in order to achieve a better understanding, a proper control, and reproducibility of the biological effects, aiming its use in human and animal medicine. The aim of this study with a theoretical approach was to determine whether the interpretation of results of the antibacterial activity of three propolis extracts from different botanical origins could be the same or not before standardization. The three samples of propolis (poplar propolis and red and green propolis) were extracted identically and their antibacterial activity was tested against Streptococcus agalactiae (Gram+) and Escherichia coli (Gram-). Our data clearly showed that interpreting the magnitude of efficiency of the extracts was completely different when they were standardized or not regarding their total polyphenol content. This conceptual work demonstrates the need of standardizing propolis extracts before testing their biological activities.
Keywords: biological efficiency; polyphenols; Propolis; standardization